La Voie peule: entre tradition et modernité - Vesco, Sylvain (France : Free Band Production, 2007)
Intimate portraits unveil the fate of Western African Fula people. In Mali, one of the poorest countries in the world, these people are confronted with the alarming uncertainty of their future. In a Malian society in full transformation, can the traditions and the lifestyle of these semi-nomadic shepherds continue to exist while confronted with the inevitable modernization of the country?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films